Effects of experimental sleep restriction on caloric intake and activity energy expenditure - Calvin, Andrew D; Carter, Rickey E; Adachi, Taro; Macedo, Paula G; Albuquerque, Felipe N; van der Walt, Christelle; Bukartyk, Jan; Davison, Diane E; Levine, James A; Somers, Virend K (Chest, 2013)
Epidemiologic studies link short sleep duration to obesity and weight gain. Insufficient sleep appears to alter circulating levels of the hormones leptin and ghrelin, which may promote appetite, although the effects of sleep restriction on caloric intake and energy expenditure are unclear. We sought to determine the effect of 8 days/8 nights of sleep restriction on caloric intake, activity energy expenditure, and circulating levels of leptin and ghrelin. We conducted a randomized study of usual sleep vs a sleep restriction of two-thirds of normal sleep time for 8 days/8 nights in a hospital-based clinical research unit. The main outcomes were caloric intake, activity energy expenditure, and circulating levels of leptin and ghrelin. Caloric intake in the sleep-restricted group increased by +559 kcal/d (SD, 706 kcal/d, P=.006) and decreased in the control group by -118 kcal/d (SD, 386 kcal/d, P=.51) for a net change of +677 kcal/d (95% CI, 148-1,206 kcal/d; P=.014). Sleep restriction was not associated with changes in activity energy expenditure (P=.62). No change was seen in levels of leptin (P=.27) or ghrelin (P=.21). Sleep restriction was associated with an increase in caloric consumption with no change in activity energy expenditure or leptin and ghrelin concentrations. Increased caloric intake without any accompanying increase in energy expenditure may contribute to obesity in people who are exposed to long-term sleep restriction. ClinicalTrials.gov; No.: NCT01334788; URL: www.clinicaltrials.gov.